2013
DOI: 10.1371/journal.pone.0057771
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Copy Number and Risk of Oral Cancer: A Report from Northeast India

Abstract: BackgroundOral squamous cell carcinoma (OSCC) is the sixth most common cancer globally. Tobacco consumption and HPV infection, both are the major risk factor for the development of oral cancer and causes mitochondrial dysfunction. Genetic polymorphisms in xenobiotic-metabolizing enzymes modify the effect of environmental exposures, thereby playing a significant role in gene–environment interactions and hence contributing to the individual susceptibility to cancer. Here, we have investigated the association of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 54 publications
5
48
2
Order By: Relevance
“…The content of mitochondria (mitochondrial DNA copy number) changes with the changed status of cells and may increase or decrease (59)(60)(61)(62). In the present study, we found that non-essential amino acids maintained a constant mitochondria content in gastric cancer cells undergoing glucose starvation, which indicates that non-essential amino acids may reduce the decreasing effect on the content of mitochondria that are induced by glucose starvation and thus sustain cell viability (63).…”
Section: Discussionsupporting
confidence: 59%
“…The content of mitochondria (mitochondrial DNA copy number) changes with the changed status of cells and may increase or decrease (59)(60)(61)(62). In the present study, we found that non-essential amino acids maintained a constant mitochondria content in gastric cancer cells undergoing glucose starvation, which indicates that non-essential amino acids may reduce the decreasing effect on the content of mitochondria that are induced by glucose starvation and thus sustain cell viability (63).…”
Section: Discussionsupporting
confidence: 59%
“…The reported HPV prevalence in oral cancers in India varied from 0 to 100% in studies using biopsies in cases and PCR assay for HPV detection and genotyping. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] For the studies using a methodology similar to ours (oral brushing to collect epithelial cells instead of biopsy, combined with PCR for detection and genotyping), the prevalence reported for oral cancer cases was 31.5 26 and 32.4%. 15 Our results are in agreement with two studies conducted in Gujarat and Mumbai in West India, which reported a null prevalence of HPV in oral cancer using biopsies (in one of the studies, only HPV-16 and 18 were tested).…”
Section: Discussionmentioning
confidence: 99%
“…12 One-on-one semistructured interviews using a questionnaire and life grid technique, which has been shown to improve recall, 13 were conducted by three professionally trained dentists. Data collected included sociodemographic information, religious beliefs, environmental variables and sexual behavior including age at first sexual intercourse, number of sexual partners and oral sex practice frequency during three different life stages ( 16,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and >30 years).…”
Section: Patient and Data Collectionmentioning
confidence: 99%
“…Both RNA and cDNA concentrations were determined spectrophotometrically (Biorad Spectronanodrop). The primer sequences included sense 5'-ATTGTTCCGTTCTTCTTGACTT-3' and antisense 5'-AGTGTGATGTGAAGGATTATG-3' for ARG1 (148bp), sense 5'-GGTCCCGCTGCCATAAGAG-3' and anti-sense 5'-CGTGGATTCACTATCAGGTTGTTG-3' f o r A R G 2 ( 1 3 7 b p ) , s e n s e 5'-GGATCCAAATGTGGCTGCGTTCAT-3' and antisense 5'-AACAGCCAGCCATCTACCAGTTCT-3' f o r O A T ( 1 7 5 b p ) , s e n s e 5'-GTGGGTGATTGGATGCTCTTTG-3' and anti-sense 5'-AGGCCCTGACATCACATAGTAG-3' for ODC (108bp), sense 5'-GAAATCCCATCACCATCTTCC-3' and anti-sense 5'-GAGCCCCAGCCTTCTCCATG -3 ' f o r G A P D H ( 1 2 0 b p ) , a n d s e n s e 5'-TGGATCAGCAAGCAGGAGTATG-3' and antisense 5'-AAGAAAGGGTGTAACGCAACTAAG-3' for β-actin (98bp) (Bergeron et al, 2007;Wolf et al, 2007;Haenisch et al, 2008;Kitowska et al, 2008;Kim et al, 2012;Mondal et al, 2013). For all analysis, sqPCR assays were performed in a 25 µL system containing PCR master mix, 30ng first-strand cDNA template and 0.4 µM appropriate primers.…”
Section: 7031 Modulation Of L-arginine-arginase Metabolic Pathway Enmentioning
confidence: 99%